The Use of the Social Networking Sites as a Communication Strategy for Costa Del Sol as a Tourist Destination. - Pérez-Tapia, Gema; Cestino González, Estefanía; Mercade-Mele, Pere; Almeida-García, Fernando (Springer Nature, 2023)
In recent years, the internet has become a fundamental source of information when planning vacations. Also, social networks have broken into our lives in a very considerable way. From the pandemic caused by COVID-19 this information transmitted through RRSS must be planned conscientiously, since it is very likely that potential tourists need a type of information that in addition to generating interest in the destination, generates security and confidence in terms of health. The main objective of this project is to analyze the image issued of the Costa del Sol through Social Networks taking as reference the information published in their RRSS (Facebook and Twitter), the most recurrent topics, the information provided about the COVID-19, the type of publication and the objective of it, among others. As main conclusions, the objective of the publication is in most cases to inform or persuade, leaving aside one of the main capabilities of the social network that is to generate reactions. Also, and in relation to the management of the crisis caused by the pandemic, there is no emphasis on generating security and trust in its audiences
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Turismo; Marketing en Internet; Redes sociales en Internet; Networks; Costa del Sol; Tourism